Diagnóstico sectorial de venta al por menor de productos farmacéuticos, de acuerdo a la clasificación industrial internacional uniforme del cantón Loja. - Balcazar Balcazar, Tania Isabel (2024)
The sectoral diagnosis provides an in-depth understanding of an economic sector's current situation and future prospects, which facilitates the implementation of effective measures and strategies for its development and sustainable growth. This research aims to conduct a sectoral diagnosis of the retail sale of pharmaceutical products in the Loja canton. The methodology had a mixed approach that allowed addressing the research question from different perspectives in a comprehensive manner by analyzing variables with a qualitative approach, such as characterizing pharmaceutical retail businesses, as well as quantitative variables, such as determining the financial indicators, averages, and statistics of the industry to which the analysis belongs. The section was characterized to define the key factors for business success. Sixteen businesses that met these characteristics necessary for the research development were considered. The business performance indicators were determined, and with the primary and secondary information, the respective calculations were made to obtain the averages and statistics of the industry sector. Finally, it is concluded that businesses in the pharmaceutical sector have a good liquidity of 1.80, the level of indebtedness is low at 37% and a yield with a ROA of 13% and a ROE of 21%. At the level of non-financial indicators in sales, it was evidenced that there is efficiency in the sales team and in inventory management, there is a high turnover that indicates efficient management, is that the company is selling its products quickly. Therefore, this sector proves to be strategic and of greater relevance to the economy.